Investigation on Metropolitan Area Networks and Optical Networks based on FTTH - Gill, Mehak (My University, 2009)
Optical networks will change the paradigms possible for tomorrow’s information systems designers by increasing the viability of network-reliant applications. It will effectively eliminate the limitations imposed by geographical boundaries. Optoelectronic technology and optical networking will become the key enablers of the future communications infrastructure through the elimination of the severe restrictions of bandwidth and bit-error rate inherent in traditional electromagnetic signal-based communications. The ability to deploy distributed data-intensive and compute intensive applications will make tomorrow’s information systems effectively seamless, and will facilitate the deployment of applications utilizing advanced voice, data, image, and video communications components. The objective of this thesis to investigate the metropolitan area networks comprising optical components such as optical cross connects, arrayed waveguide grating multiplexers, demultiplexers and the performance analysis of the Broadband Passive Optical Network (BPON) based on FTTH. The Arrayed waveguide gratings based multiplexers and demultiplexers for WDM applications prove to be capable of precise multiplexing and demultiplexing of a large number of channels with relatively low losses. The performance and feasibility for the metropolitan area network based on arrayed waveguide grating (AWG) multiplexers and arrayed waveguide grating (AWG) demultiplexers operating at the bitrate of 10 Gb/s is demonstrated. The comparative investigation and suitability of various data formats is also presented. It has been reported that RZ Raised cosine is the most suitable data format for optical network based on arrayed waveguide grating (AWG) multiplexers and arrayed waveguide grating (AWG) demultiplexers. The quality-of-service offered by the metropolitan area network which is based on optical cross connect (OXC) and arrayed waveguide grating (AWG) demultiplexer operating at 10 Gb/s with 0.1 nm channel spacing for NRZ signal transmission is demonstrated. The OXC and AWG Demultiplexers in the proposed architecture allow incremental expansion in terms of the number of wavelength channels to be transmitted. Dispersion and crosstalk are the main signal-degrading factors arising from the operation of the OXC and the effectiveness of each factor is individually investigated. The network architecture based on FTTH systems with broadband PON (passive optical networks) access is presented. The architecture targets the delivery of very high speed, end to end optical communications between the edge nodes connecting the end users. Transmission allows the simultaneous delivery of real-time applications (Voice over IP, Video) and other data-oriented applications (Internet, peer-to-peer). To optimize the bandwidth in BPON the CWDM technique for the transmission through the optical fiber path is employed. The comparative investigation and suitability of various data formats for internet and the voice over IP transmission is also presented and the three different modulations such as QAM, PSK and offset PSK for the video signal transmission are studied. It has been observed that the most suitable data format for data transmission is RZ Rectangular when QAM and PSK modulation is used for video signal modulation whereas for offset PSK modulated video signal most suitable data format is NRZ rectangular. It is demonstrated that the most suitable modulation technique is PSK modulation technique. Passive Optical Network (PON)-based Fiber-To-The-Home (FTTH) is a promising solution that can break through the economic barrier of traditional point-to-point solutions. Hence, the thesis investigates the metropolitan area networks based on optical cross connects and AWG multiplexers and demultiplexers and broadband passive optical networks based on FTTH.
M.E. (ECED)
Keywords: AWG, Multiplexers; OXC, FTTH